The potential of a targeted unilateral compound training program to reduce lower limb strength asymmetry and increase performance: a proof-of-concept in basketball - Zhang, Wenfeng; Chen, Xing; Xu, Kun; Xie, Hezhi; Chen, Jiayong; Zhu, Ziwei; Ji, Hongshen; Li, Duanying; Sun, Jian (Frontiers in Physiology, 2024)
W.Z was responsible for the experimental design and implementation, as well as the main data collection and analysis and visualization aspects, and was a major contributor to the manuscript writing; X.C provided important contributions in data analysis, interpretation; K.X provided key materials and equipment required for the experiments; H.X supervised the whole project and provided key conceptual and directional guidance; J.C provided technical support in the experimental implementation phase; Z .Z was responsible for language proofreading; H.J was involved in data analysis and interpretation of the experimental results; DL was responsible for manuscript writing, revision and confirmation of the final version; and J.S was responsible for participating in the review of the experimental design as well as the review and approval of the final paper.